Ruins of Excess: Computer Game Images and the Rendering of Technological Obsolescence. Issue 8 (December 2021) - Luersen, Eduardo H; Fuchs, Mathias
In this article, we describe three layers of ruins related to computer game technology: in a surface layer, we examine the imagery of ruins in digital games, highlighting game design tools for developing in-game ruination. Secondly, we approach the industrial design model of technological obsolescence as an infrastructural layer that intrinsically demands the production of new provisional spaces for material decay. Lastly, through a waste layer, we unfold the geopolitical dimension of technological obsolescence, calling attention to the transcontinental flows of electronic waste, which also underscores a geological stage of ruination. While exploring these different layers of ruins, we wish to perceive how game design models might relate to different forms of contemporary ruination, inquiring what such material traces have to say as strata of the complex deterioration processes of present-day media.